2021
DOI: 10.1155/2021/8268755
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myopericarditis after COVID-19 Vaccine in Teenagers

Abstract: Background. There have been an increasing number of reports of myocarditis and pericarditis in adolescents and young adults after coronavirus disease 19 vaccinations. The pathophysiology of myocarditis after this vaccination is indeterminate currently. The problem is a relatively new phenomenon, and so there are no current guidelines on how to manage these cases of myopericarditis. We intend to describe our management in these two cases so that it can help guide pediatricians, intensivists, and cardiologists t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Further review identified a total of 57 studies reporting cases, case series, and summated case series of COVID‐19 vaccine‐associated myocarditis. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 59 , 60 , 61 , 62 , 63 , …”
Section: Resultsmentioning
confidence: 99%
“…Further review identified a total of 57 studies reporting cases, case series, and summated case series of COVID‐19 vaccine‐associated myocarditis. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 59 , 60 , 61 , 62 , 63 , …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the incidence of myocarditis following the infection with SARS-CoV-2 is estimated to be 40 per million [10] . Additionally, there has been no evidence suggesting an increased risk of postvaccination pericarditis or cardiac arrhythmias, with the exception of those who received their second dose of the mRNA-1273 vaccine [11] . However, the risk of myocarditis, pericarditis, and cardiac arrhythmia was increased following SARS-CoV-2 infection in the same population [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Both patients were admitted to the pediatric intensive care unit for continuous cardiopulmonary monitoring, including trending troponin, brain natriuretic peptide, erythrocyte sedimentation rate, and C-reactive protein every eight hours. They were supportively managed with acetaminophen, Ibuprofen, famotidine, lidocaine, and intravenous fluids [ 6 ]. Both patients recovered promptly and were at pre-morbid baseline on outpatient follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Both patients recovered promptly and were at pre-morbid baseline on outpatient follow-up. Well-known etiologies of myopericarditis are marijuana inhalation, viral, autoimmune, neoplastic lesion, post-infarction, and post-vaccination [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%